System-wide school mindfulness: addressing elementary students’ social-emotional learning and wellbeing - Henriksen, Danah; Gruber, Natalie (Frontiers in Education, 2024)
When considering students' educational needs, emotional and mental health are often lower school priorities than content learning and traditional curricula. Yet, a growing youth mental health crisis is a reality that educators cannot afford to ignore. In this article, we present an illustrative case, at the school community level, as a form of pedagogical innovation. In this practical article, we discuss how a disenfranchised school community incorporated a systemic mindfulness intervention into its school culture, yielding positive and impressive results. Based on teachers' pedagogical perspectives, we share perceptions of changes in students' behavior, mental health, general outcomes, and teacher retention. This was spurred by a need to support students' emotion regulation at school. We situate this local community innovation within the larger issue of youth mental health within U.S. society and education. We describe the local context and setting of the school, including the need for trauma-informed socialemotional support for students with significant needs. After describing the mindfulness innovation in detail, we then share our qualitative analysis and results of its impact. Discussing interviews with school staff and administrators, and our observations of the school and classrooms, we distill findings and offer insights about the outcomes of mindfulness used at the level of an entire school community. Our implications suggest the potential of such community mental/emotional health innovations in education for students and teachers, leading to multiple areas of school improvement.